Peran Permainan Tradisional dalam Pendidikan Anak Usia Dini - Evi Rahayu (Departement of Mathematics Education, 2023)
Early childhood education serves a significant role in fostering the cognitive, social, and motor skill development of young children. For ages, traditional games have been an integral aspect of human society and are widely recognised as a significant element in the realm of early childhood education. The primary objective of this study is to elucidate the significance of traditional games within the context of early childhood education. The research methodology employed in this study involves doing a comprehensive review of relevant literature. The findings of this study indicate that traditional games designed for early childhood have the potential to enhance the development of imagination and creativity, enhance spatial reasoning and visualisation skills, foster social interaction and collaborative engagement, improve fine motor skills and hand-eye coordination, and instill a sense of achievement and self-confidence.